Pengaruh Return on Assets, Return on Equity, Net Profit Margin, Earning per Share dan Debt to Equity Ratio Terhadap Dividend Payout Ratio Pada Perusahaan LQ45 Yang Terdata Di BEI Tahun 2022-2024 - Maspupah, Hidayatul; Izzati, Fauziana Nur; Riyanto, Dimas; Fitriani, Neris Eka; Diniati, Bintis Tianatud (Jurnal Manajemen dan Investasi (MANIVESTASI), 2025)
ABSTRACT This study aims to find out about the effect of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Earning Per Share (EPS), Debt To Equity Ratio on Dividend Policy in Companies Listed in the LQ 45 Index on the Indonesia Stock Exchange (IDX) Period 2022 - 2024. This type of research is quantitative descriptive research. The population of this study were 45 companies. A sample of 38 companies was determined from the method of multiple regression data analysis techniques through classical assumption testing. The data analysis methods used are descriptive statistical tests, classical assumption tests (normality tests, multicolonierity tests, heteroscedasticity tests and autocorrelation tests), multiple linear regression analysis, determination coefficient tests, hypothesis tests (T tests and F tests) through the help of the IBM SPSS Statistic Version 16 program. The results showed that simultaneously Return on Assets (ROA), Net Profit Margin (NPM), Earning per Share (EPS), Debt to Equity Ratio (DER) had an effect on Dividend Policy. Partially, only Earning per Share has an effect on Dividend Policy. For investors who want to invest, they must see information about financial ratios, because the data is important in estimating the amount of dividends that will be received. Keywords : ROA, ROE, NPM, EPS, DER, Dividend Payout Ratio ABSTRAK Penelitian ini memiliki tujuan guna mengetahui tentang pengaruh Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Earning Per Share (EPS), Debt To Equity Ratio terhadap Kebijakan Deviden Pada Perusahaan Yang Tercatat Dalam Indeks LQ 45 Di Bursa Efek Indonesia (BEI) Periode 2022 – 2024. Jenis penelitian ini ialah penelitian deskriftif kuantitatif. Populasi penelitian ini ialah 45 perusahaan. Sampel sejumlah 38 perusahaan ditetapkan dari metode teknik analisis data regresi berganda melalui pengujian asumsi klasik. Metode analisis data yang dipergunakan yaitu uji statistik deskriptif, uji asumsi klasik (uji normalitas, uji multikolonieritas, uji heteroskedastisitas serta uji autokorelasi), analisis regresi linier berganda, uji koefisien determinasi, uji hipotesis (uji T dan uji F) melalui bantuan program IBM SPSS Statistic Version 16. Hasil penelitian memperlihatkan secara simultan Return on Assets (ROA), Net Profit Margin (NPM), Earning per Share (EPS), Debt to Equity Ratio (DER) berpengaruh terhadap Kebijakan Dividen. Secara parsial hanya Earning per Share yang berpengaruh terhadap Kebijakan Dividen. Untuk investor yang hendak berinvestasi, harus melihat informasi mengenai rasio keuangan, dikarenakan data itu penting dalam memperkirakan jumlah dividen yang nantinya akan diterima. Kata Kunci: ROA, ROE, NPM, EPS, DER, Dividend Payout Ratio